The Design Method of Axial Flow Runners Focusing on Axial Flow Velocity Uniformization and Its Application to an Ultra-Small Axial Flow Hydraulic Turbine. (1st December 2016) - Nishi, Yasuyuki; Kobayashi, Yutaka; Inagaki, Terumi; Kikuchi, Norio
Abstract : We proposed a portable and ultra-small axial flow hydraulic turbine that can generate electric power comparatively easily using the low head of open channels such as existing pipe conduits or small rivers. In addition, we proposed a simple design method for axial flow runners in combination with the conventional one-dimensional design method and the design method of axial flow velocity uniformization, with the support of three-dimensional flow analysis. Applying our design method to the runner of an ultra-small axial flow hydraulic turbine, the performance and internal flow of the designed runner were investigated using CFD analysis and experiment (performance test and PIV measurement). As a result, the runners designed with our design method were significantly improved in turbine efficiency compared to the original runner. Specifically, in the experiment, a new design of the runner achieved a turbine efficiency of 0.768. This reason was that the axial component of absolute velocity of the new design of the runner was relatively uniform at the runner outlet in comparison with that of the original runner, and as a result, the negative rotational flow was improved. Thus, the validity of our design method has been verified.